Some Spiny Backed Orb-Weaving Spiders (Araneae: Araneidae) From Bangladesh - Biswas, -; Raychaudhuri, V; Raychaudhuri, D (Journal of Biodiversity Conservation and Bioresource Management, 2021)
Spiny backed orb-weaving spiders sampled from different areas of Khulna and Bagerhat, Bangladesh were dealt with. Three species of the genus Gasteracantha Sundevall were recorded that includes one new species G. chowdhuryi n. sp. Generic diagnosis, illustrated description and distribution together with key to the species were provided herewith. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(2): 35-46